Predictors of return to work and employment in cancer survivors: a systematic review. Issue 2 (26th December 2012) - van, P.; Weevers, N.L.E.C.; Snels, I.A.K.; Duijts, S.F.A.; Bruinvels, D.J.; Schellart, A.J.M.; van der, A.J.
<x xml:space="preserve">Abstract</x> The objective of this study was to provide an overview of the prognostic factors for return to work and employment of cancer survivors. Cohort studies were selected if the population consisted of cancer patients between 18 and 65 years of age, with return to work, employment or equivalent concepts as main outcome measure, studying at least one prognostic factor. The methodological quality of the included studies and level of evidence for each prognostic factor were assessed. Twenty‐eight cohort studies met the inclusion criteria. Heavy work and chemotherapy were negatively associated with return to work. Less invasive surgery was positively associated with return to work. Breast cancer survivors had the greatest chance of return to work. Old age, low education and low income were negatively associated with employment. Moderate evidence was found for extensive disease being negatively associated with both return to work and employment, and for female gender being negatively associated with return to work. The review shows that in cancer survivors, a limited number of prognostic factors of return to work and employment can be identified. Physicians primarily engaged in the process of vocational rehabilitation of cancer survivors should be aware of the potential role these factors exert.